Study and analysis of land tax and land premium between Penang and Perlis / Muhammad Muzzamil Mahmuddin - Mahmuddin, Muhammad Muzzamil (2018)
This research reviews the study of issue non-uniformity estimation of rate land tax and land premium in Perlis and Penang. The aim of this study to model the land tax and land premium in Perlis and Penang using AutoCad 2013 software. This study focuses on the Perlis and Penang as researchers want to know the extent of these differences for developed and developing states. The results of data obtained by government agencies involved such as the Land and Mines Office (PTG), the Department of Valuation and Service of Property (JPPH) and city planning units in these two states have been collected and analyzed according to the proposed methodology. In addition, to make a map of the study area, researchers need to take sample maps at the urban planning unit and need to be digitized again for the purpose of differentiating the land tax rate in these two states. This research also want to identify the formula that has been using by State Authorities to determine the rate land tax and land premium in Perlis and Penang in term of type of land (agricultural, building and industry), location, and size of the land. Both state authorities in Perlis and Penang have difference in land administrative and rate of land premium charge for the purpose of conversion the land. Hence, there have some factor that need to be consider to determine the rate of land tax and land premium. All related to land is the state's jurisdiction. The state government have a power to determine tax land and land premium of the local population in their respective states in term of type of land, location (city, town and village), and size of the land. The result of this study is to show the difference between two states in Perlis and Penang based on the land tax rate. Different colors on the map show different rates.